Mobile Wireless Middleware Operating Systems and Applications. Second International Conference, Mobilware 2009, Berlin, Germany, April 28-29, 2009. Proceedings - Bonnin, Jean-Marie (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2009)
This book constitutes the thoroughly refereed proceedings of the Second International Conference on MOBILe Wireless MiddleWARE, Mobilware 2009, held in Berlin, Germany, in April 2009. The 29 revised full papers presented were carefully reviewed and selected from 63 contributions. The papers are organized in topical sections on location and tracking supports and services; Location-aware and context-aware mobile support and services. middleware for QoS awareness, adaptation, and fault-tolerance of mobile services; mobility-aware wireless service discovery, management, and delivery; middleware for mobile computing & Intelligent and mobile agent technologies for mobile systems and services; OS/middleware for embedded systems, wearable networks, and personal area networks; mobility management and handoff management in heterogeneous networks.